Micromorphology of the elytral cuticle of beetles, with an emphasis on weevils (Coleoptera: Curculionoidea). Issue 1 (January 2016) - van de Kamp, Thomas; Riedel, Alexander; Greven, Hartmut
Abstract: The elytral cuticle of 40 beetle species, comprising 14 weevils (Curculionoidea) and 26 representatives of other taxa, is examined. All weevils and 18 other species have an endocuticle with prominent macrofibers, which corresponds to a modified pseudo-orthogonal cuticle. Angles between successive layers of macrofibers range between 30° and 90°, but are constantly less than 60° in weevils. In all Curculionoidea, as well as in one buprestid and one erotylid species exo- and endocuticle are densely interlocked. In the weevil Sitophilus granarius, transmission electron microscopy revealed vertical microfibrils extending from the exocuticle between the macrofibers of the underlaying endocuticle. Vertical microfibrils connecting successive macrofiber layers of the endocuticle were observed in S. granarius and Trigonopterus nasutus . Distinct cuticular characters are traced on a beetle phylogeny: the angles between unidirectional endocuticle layers; the presence and the shape of endocuticular macrofibers; and the interlocking of exo- and endocuticle. While character traits seem to be more or less randomly distributed among Coleoptera, the Curculionoidea have a uniform groundplan: The "weevil-specific" combination of characters includes 1) interlocking of exo- and endocuticle, 2) an endocuticle with distinct ovoid macrofibers embedded in a matrix and 3) comparatively small angles between successive endocuticular layers. Thus, phylogenetic constraints appear equally important to functional factors in the construction of the weevil elytron. Highlights: We compare the elytral cuticle of 40 beetle species, including 14 weevils and trace distinct characters on a phylogeny. Most species show an endocuticle with prominent macrofibers. Microfibrils extending from the exocuticle between macrofibers or connecting macrofiber layers were observed in weevils. In all weevils and two other species, exo- and endocuticle are densely interlocked. We suggest a "weevil-specific" combination of cuticular characters.